ANTIBACTERIAL THERAPY OF ACUTE OTITIS MEDIA IN CHILDREN: MODERN APPROACH - L. I. Usenya; E. P. Karpova ("Paediatrician" Publishers LLC, 2012)
The problem of acute otitis media is discussed in this article. The authors describe the main concepts of antibacterial treatment with the culture and antibiotic susceptibility testing of tympanic exudate being the «gold standard» in medicine choosing. The choosing of antibacterial agent is a critical point and demands an increased care. The antibiotic must be broad-spectrum, have minimal side-effects and be of a convenient use form. The possibility of resistance development must be also minimized. The data on clinical efficacy and good tolerance of the macrolide antibiotic clarithromycin in treatment of acute otitis media in children are represented in the article. This medicine can be recommended as a drug of choice in treatment of acute otitis media.